(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The purpose of the article is to reveal the pattern of naming people by the age group to which they belong in the English language. The research material is data from etymological and explanatory dictionaries, as well as corpora of the English language. The author uses etymological analysis, the method of semantic oppositions and considers age nominations in English and Russian languages within the framework of a cognitive context.